English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I need help with this math problem
If the product of 5 and a number is increased by 9 and this sum multiplied by 3, the result is 11 greater than the opposite of the number. Find the number.

2006-12-06 11:31:40 · 7 answers · asked by Anonymous in Science & Mathematics Mathematics

(5)(n)+9)(3)= 11+-n

2006-12-06 11:41:45 · update #1

i need to know what number is n(as u call it x)

2006-12-06 11:44:51 · update #2

7 answers

(5n+9)3=-n+11

15n+27=-n+11
15n=-n-16
16n=-16
n=-1

2006-12-06 11:44:02 · answer #1 · answered by Anonymous · 1 0

All you have to do is interpret this into an equation.

First, the word product implies multiplication, so all we are doing is multiplying an unknown number, x, by 5. So we represent this symbolically as 5x. To increase a number means to add something to it. That means we just add 9 to 5x. So, now we have 5x+9. This sum is multiplied by 3. So we now write it as 3(5x+9).

Next it tells us that the result above, 3(5x+9), is 11 greater than the opposite, or negative, of x. That implies this relationship between 3(5x+9) and -x:

3(5x+9) = -x+11.

Now all we have to do is the algebra to find the number.

15x+27 = -x+11
15x+x = 11-27
16x = -16
x = -1

Substitute this number back into 3(5x+9) = -x+11 and see if it produces a true statement. If it does, then one side will equal the other, and the answer is correct.

2006-12-06 12:04:52 · answer #2 · answered by MathBioMajor 7 · 1 0

The problem has been written by you as (5n+9)*3=11-n.
That is 15n+27=11-n. Adding n to both sides, 16n+27=11 0r
16n=11-27=-16. So n=-16/16=-1.

2006-12-06 11:49:10 · answer #3 · answered by greenhorn 7 · 1 0

number = x

product of 5 and x = 5x

increased by 9 means 5x +9

this sum multiplied by 3: 3(5x+9)

the result is meas use and equals sign

3(5x+9) = ?

the opposite of x is -x
eleven more is -x + 11

the whole thing is:
3(5x+9) = -x + 11

solve
15x + 27 = -x + 11
16x + 27 = 11
16x = -16
x = -1

(misread the question earlier)

check
3(5(-1) + 9) = -(-1) + 11
12 = 12

answer checks out

2006-12-06 11:45:15 · answer #4 · answered by Steve 5 · 0 0

3((5 x n) + 9)= 11 - n
innermost guts: 3(5n + 9)=11-n
next: 15n + 27=11 - n
then: 15n + n= 11-27
...:16n=-16
finally: n=-1
hope i helped some : )

2006-12-06 11:52:18 · answer #5 · answered by saljkglwyt 2 · 1 0

First, state all information 3(5x+9)=11(-x) next, distribute the 3 and 15x+27=-11x then x on one side 27=-11x-15x , combine 27=-26x divide by -26 on both sides = -(27/26)=x

2006-12-06 11:40:52 · answer #6 · answered by card19 1 · 1 1

((5xn)+9)x3-11=-n

I'm guessing you mean negative for opposite?

(15n + 27) = -n + 11

16n = -16

n = -1

2006-12-06 11:35:32 · answer #7 · answered by Anonymous · 0 1

fedest.com, questions and answers